Competency-based approach in technical education: a case study on ITSC and INFOTEP in the Dominican Republic - Martínez-Nova, Juan Antonio (2024)
The main objective of this study is to assess the relevance of the competency-based approach in teaching practices within technical and vocational education in the Dominican Republic. The focus is on two institutions: the Instituto Técnico Superior Comunitario (ITSC) and the Instituto Nacional de Formación Técnico Profesional (Infotep). The study participants included both students and teaching staff from these institutions. The findings reveal that both ITSC and Infotep are highly regarded across the measured indicators, particularly in the category of pedagogical aspects.